Approaches to the analysis of accident risk on roads. A systematic review of the literature - Cano Condori, Harold Gaspar (LACCEI, 2024)
This literature review seeks to clarify the way in which the relationship between geometric design and the risk of accidents on roads is addressed. To this end, information was collected from 40 open access articles from journals indexed in Scopus, these articles were published in English between the years 2000 and 2023. It was found that more than 90% of them consider that the geometric design of roads has direct effects on the probability of accidents occurring, 52.5% of the articles analyzed use approaches that consider statistical methods while other approaches such as those that consider environmental factors or minor vehicles such as motorcycles and bicycles represent less than 5% of the studies analyzed.